Modeling the Symptom-Disease Relationship by Using Rough Set Theory and Formal Concept Analysis - Bal, Mert; Sever, Hayri; Kalipsiz, Oya (WORLD ACAD SCI, ENG & TECH-WASET, 2007)
Medical Decision Support Systems (MDSSs) are sophisticated, intelligent systems that can provide inference due to lack of information and uncertainty. In such systems, to model the uncertainty various soft computing methods such as Bayesian networks, rough sets, artificial neural networks, fuzzy logic, inductive logic programming and genetic algorithms and hybrid methods that formed from the combination of the few mentioned methods are used. In this study, symptom-disease relationships are presented by a framework which is modeled with a formal concept analysis and theory, as diseases, objects and attributes of symptoms. After a concept lattice is formed, Bayes theorem can be used to determine the relationships between attributes and objects. A discernibility relation that forms the base of the rough sets can be applied to attribute data sets in order to reduce attributes and decrease the complexity of computation.
Keywords: Formal Concept Analysis; Rough Set Theory; Granular Computing; Medical Decision Support System; Computer Science; Engineering